STUDI INTERAKSI FISIKA ITRAKONAZOL - ASAM MALONAT DAN ASAM MEFENAMAT - ISONIKOTINAMID - Yuyun, Yonelian
Background and Purpose: Solid-solid interaction in the form of physics and chemistry can occur in a combination of active ingredients with the active ingredient or active ingredients with excipients in a pharmaceutical preparation. Physical interactions can be classified into physical interaction system eutectikum, peritecticum, and molecular compounds based on the phase diagram of a mixture of two-component systems. Itraconazole and malonic acid has been reported to have interactions as molecular compounds/co-crystal and has been isolated by the method of solvent drop grinding and slow evaporation. While the physical interaction between mefenamic acid and isonicotinamid not been reported previously. This study aims to isolate physical interaction of itraconazole (ITZ) with malonic acid (MAL) using other techniques, namely liquid antisolvent and examine the type of interaction of mefenamic acid (AM) with isonicotinamid (INA) and its interaction with the isolation methods by solvent drop grinding as the simplest method and easy to do. Next observation is how the effect of the interaction on the hygroscopicity formation and solubility of active ingredients. Methods : Conduction of formation physical interaction by making the phase diagram of the melting temperature data in a combination of both physical mixture ratio - 0:10; 1 :9•, 2:8•, 10:0 by Electrothermal. Furthermore, of itraconazole with malonic acid (2:1) was prepared by liquid antisolvent method and physical interaction of isonicotinamid and mefenamic acid (l : 1) was isolated by solvent-drop grinding method using ethanol and ethyl acetate. Characterization of the interaction physics is done by melting point ana\ysis (Electrothermal 9100), Differential Thermal Analysis (DTA), and X-iay powder diffraction (PXRD). In the next phase solubility analysis both active ingredients in the form of some sort of physical interaction using a UV spectrophotometer; and hygroscopicity test with storage of physical interaction results in a desiccator with a relative humidity of 99% using a Karl Fischer Titration as the method of determination of water content. Results : From the melting point data using a Electrothermal obtained phase diagram is formed curve indicating the formation of molecular compounds ITZ-MAL and AM-INA. PXRD data showed a new peak in the mixture of ITZ- MAL interaction at 20: 8,671; 10,080; 14,4090, whereas the interaction of AMINA mixture contained no new peaks, so the indicated AM - INA only form of eutecticum interaction. For the data of ITZ-MAL DTA discovered a new endothermic peak at 1670C and AM-INA at 149,5 0C (SDG-Ethanol) and 148,4 0 C (SDG-Ethyl acetate). For the data of ITZ-MAL thermogram discovered a new endothemic peak at 1670C and AM-INA at 149,5 0C (SDG-Ethan01) and 148.40C (SDG-Ethyl acetate). The results of infrared spectroscopy analysis indicated a shift in the OH stretch of 2927 cm-I to 2923 cm-I , CN stretch of 1457 cm-I to 1454 cm- and stretch of 1612 cm-I to 1623 cm-I at ITZ - MAL. While the AMINA, a shift ofthe NH stretch 3367 cm-I to 3359 cm-I ; and 3185 cm-I to 3178 cm The solubility of ITZ and AM increased with each mixing method, the level of hygroscopicity be higher than a single component. Conclusion: The formation of molecular compounds / co-crystals of itraconazole - malonic acid (2:1) can be carried out by the method of liquid antisolvent. The results of physical interactions itraconazole - malonic acid showed a typical peak 20: 8,671; 10,080; 14,409 0 and has a melting temperature of 164 0 C. Results of physical interaction of itraconazole with malonic acid has two times higher solubility than single itraconazole. On the other hand, the result of the interaction increases the hygroscopicity compared itraconazole Mefenamic acid and isonicotinamida formed physical interaction eutecticum in a ratio of 1 : 1 with solvent drop grinding methods. This interaction has a melting temperature of 148,4 to 149,5 0 C and did not show the typical peaks in the difractogram compared to physical mixtures. Results of physical interaction mefenamic acid — isonicotinamida has a solubility 60 times higher than the mefenamic acid as a single compound. Hygroscopicity test shows the results of these interactions has a level higher of water content.